(untitled) - Pessarakli, Mohammad (London, 2005)
A completely updated reworking of the critically acclaimed first edition, this handbookdiscusses photosynthesis under normal and stressful conditions, covering biochemistry and molecular biology for both lower and higher plants. Providing nearly 8000 bibliographic citations, and filled with drawings, photographs, tables, and equations, the handbook contains authoritative contributions from more than 80 scientists. It relates photosynthesis to plant production and crop yields, presents the plant genetic factors affecting photosynthesis, examines mathematical models and response functions of photosynthesis, and analyzes the spatial and temporal relationships between respiration and photosynthesis.
Keywords: Photosynthesis